2020
DOI: 10.1002/bjs.11373
|View full text |Cite
|
Sign up to set email alerts
|

Effect of radiotherapy for rectal cancer on female sexual function: a prospective cohort study

Abstract: Background Clinical experience and limited data show that female sexual function is influenced negatively by preoperative radiotherapy (RT) for rectal cancer. The aim of this prospective study was to investigate the impact of RT on sexual function and ovarian reserve measured by levels of anti‐Müllerian hormone (AMH). Methods Women with stage I–III rectal cancer scheduled for surgery with or without preoperative (chemo)RT were included and followed for 2 years. Female Sexual Function Index (FSFI) questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…36 The observed decrease in sexual function and the increased prevalence of FSD are consistent with earlier findings. 1,5,13,34,37 The present study's main findings are the associations between the androgens T and A-4 with overall sexual function, lubrication, and orgasm, and A-4 with arousal and pain/discomfort. The association between endogenous T and overall female sexual function is not well described in the literature before.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…36 The observed decrease in sexual function and the increased prevalence of FSD are consistent with earlier findings. 1,5,13,34,37 The present study's main findings are the associations between the androgens T and A-4 with overall sexual function, lubrication, and orgasm, and A-4 with arousal and pain/discomfort. The association between endogenous T and overall female sexual function is not well described in the literature before.…”
Section: Discussionmentioning
confidence: 54%
“…2,3,9 Preoperative radiotherapy induces cell death, inflammation, ischemia, and radiation fibrosis in exposed tissues, 10 and thereby an increased risk of vaginal dryness, narrowing and stenosis, and radiation-induced menopause in premenopausal women. [11][12][13][14] An association between radiotherapy for pelvic cancer and decreased ovarian androgen production in non-oophorectomized patients has been reported, [15][16][17] similar to the decrease seen after oophorectomy. 17 Androgens seem to play an important role in female sexual function.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Age, tumor location, use of preoperative radiotherapy, the operation method and the stoma can affect postoperative urogenital function [ 5 , 21 23 ]. Havenga K reported that [ 24 ] more than 86% of patients under 60 years of age were sexually active, while only 60% of patients over 60 years of age were sexually active; thus, in this study, we only included patients who were sexually active one month before surgery and were younger than 60 years old.…”
Section: Discussionmentioning
confidence: 99%
“…It follows that young patients with rectal cancer are those who may benefit most from more aggressive neoadjuvant treatment, if a complete response and organ preservation can be achieved. However, if rectal resection will ultimately be required, despite neoadjuvant radiotherapy, this group may also have most to lose from the digestive, urological and sexual function point of view, if irradiation could safely have been avoided. Concern also exists about the use of radiotherapy in young patients because of the increased risk of late toxicity and potential future secondary cancer, reported as 5 per cent at 12 years' follow‐up in the Dutch trial.…”
Section: Management Challenges In Rectal Cancermentioning
confidence: 99%